A fast and energy-efficient two-stage level shifter using the controlled Wilson current mirror. (2nd October 2017) - Maroof, Naeem; Sohail, Muhammad; Shin, Hyunchul
ABSTRACT: Multiple voltage domains are commonplace in modern SoCs and level shifter (LS) circuits allow different voltage domains to be interfaced with each other. As the reduced supply voltages are extensively used in digital blocks for low-power operation, the conversion of sub-threshold voltage levels to full VDD signal becomes a particular problem. In this paper we present a new LS structure for the fast and energy-efficient conversion of extremely low voltage levels. The proposed LS is a two-stage structure consisting of a controlled Wilson current mirror and eliminates the negative feedback mechanism. Inverted output of the second stage controls the current through the first stage. If the input signal is logical high (VDDL) then the circuit will produce high output (VDDH) and the first stage is prepared to conduct the current for logical 0 input (0V). This improves the slew rate problem and enables fast and energy-efficient operation. Considering process corners at a 90-nm technology node, the proposed design reliably converts 150-mV input signal into 1 V output signal. Post-layout results show that the proposed LS exhibits a propagation delay of 16 ns, a total energy per transition of only 79 fJ, and a static power dissipation of 16.6 nW for a 200 mV input signal at 1-MHz, while loading 100 fF of capacitive load.